Küresel Boyutta Yoksulluk ve Kadın Yoksulluğu (Poverty On A Global Scale And Women Poverty) - Gülşen GERŞİL (Yönetim ve Ekonomi, 2015)
As a result of the neo-liberal policies together with the globalization process, poverty in contrast with prosperity and wealth being seen in all over the world has still deepened has been identified by international researchs carried out. Today, the fact that the human needs are not only limited to material dimension but also there are their dimensions in spiritual qualities, cannot be ignored.Definition of poverty, also contains satisfaction of the so-called needs which are not in material quality, has the stiuation further complicated and the failure to be found a completely definition of poverty stems fromranging according to time and space or being addressed in terms of multi-dimensionally. In the framework of human rights;by virtue of being human; mainly the right to life and liberty, including health, education, food, shelter and social services; a healthy lifestyle; being entitled to equal protection of the laws form of the basis of Universal Declaration of Human Rights. As a phenomenon in the global dimension, the problem of poverty has been threatened these owned G. Gerşil / Küresel Boyutta Yoksulluk ve Kadın Yoksulluğu 160 rights has been observed. This situation is inevitable for especially women among disadvantaged groups who intensely feel the severity of poverty. For women, labor market participation is low and educational opportunities are very limited, the state of being woman that social gender roles are shaped, being trained with the traditional female role model, sufficient time is not left to woman in order to generate income, have caused that they limited benefit from the human rights. Discriminatory attitudes towards women in the labor market also have increased the poverty of women. All of these factors,cause that the women povertyhas been worsened, continued over the generations and been permanent. In this context, the most important factor that can reduce women poverty is socio-economic policiesrelated to the inclusion of more women in working life. In light of these statements, after explaining the incidence of poverty and women’s poverty concepts and their importance, by determining the causes of women's poverty, what size women’s poverty has in our country besides in the world and the employment and social policies that can be applied for it will be placed in this study.